2010
DOI: 10.1108/17554211011074047
|View full text |Cite
|
Sign up to set email alerts
|

A service quality evaluation scale for the hospitality sector

Abstract: PurposeThe purpose of this paper is to present a scale for service quality evaluation in the hospitality sector. This scale has two aims: to assess the dimensions and attributes consumers use when evaluating the quality of the service provided by hotels, and to determine what influence service quality perceptions have on consumer behaviour, namely on customer intentions to return and to recommend the hotel.Design/methodology/approachThe methodology used to develop the scale was divided into three stages: first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…The second part of the questionnaire pertains to the measurement of the demographic characteristics of respondents. The adopted instrument was in line with previous studies by Tribe and Snaith (1998), Khan (2003) Narayan et al (2008) and Salazar et al (2010). A pilot test was conducted with 25 instructors at Cumhuriyet University.…”
Section: Methodsmentioning
confidence: 80%
“…The second part of the questionnaire pertains to the measurement of the demographic characteristics of respondents. The adopted instrument was in line with previous studies by Tribe and Snaith (1998), Khan (2003) Narayan et al (2008) and Salazar et al (2010). A pilot test was conducted with 25 instructors at Cumhuriyet University.…”
Section: Methodsmentioning
confidence: 80%
“…Salazar, Costa, and Rita (2010) stressed the importance of both research from consumers and non-consumers. Accordingly, "research from consumers tells us about a firm's strengths and weaknesses.…”
Section: Service Quality Definedmentioning
confidence: 98%
“…In terms of theoretical contributions, the use of a service quality model has contributed to the literature by investigating the differences in hotel service quality attributes between the two types of hotel. As suggested by Salazar et al (2010), this study could contribute in the areas of both consumer decision-process theory and service marketing literature focusing on customer satisfaction. It includes the different customer groups requiring different management strategies in order to achieve excellent service quality.…”
Section: Introductionmentioning
confidence: 99%
“…Carrillat et al (2007) found that SERVQUAL was a well-known instrument, and became a proper measurement tool for the hotel business, one of the service businesses focusing on customer satisfaction. Salazar et al (2010) also developed a service quality evaluation scale for the hospitality sector.…”
Section: Service Quality Measurement In the Hotel Businessmentioning
confidence: 99%